Data management of Triple Quorum Replication (TQR) for data grid - Latip, Rohaya; Hanandeh, Feras Ahmad Hamid; Abd Wahab, Mohd Helmy; Mizan, Tazquia (Universiti Utara Malaysia, 2012)
Grid computing is essentially distributed computing over wide-area networks that often involve large scale resource sharing among collaborations of individuals or institutes. Computational Grids address computationally intensive applications that deal with complex and time consuming computational problems on relatively small data sets, whereas Data Grids address data intensive applications that deal with the evaluation and mining of large amounts of data in the terabyte and petabyte range. By having large number of data in a complex computing structure such as grid requires a good data management protocol. In this paper, Triple Quorum Replication (TQR) protocol was introduces for grid environment and compares its results of data availability with Enhanced Diagonal Replication 2D Mesh (EDR2M). A simulation of Triple Quorum protocol is developed using Java and results has proven that the TQR has higher data availability compare to EDR2M.